Analysis of Mercury Heavy Metal Content in Tilapia (Oreochromis niloticus) From Rawa Taliwang Lake - Khairuddin, Khairuddin; Yamin, M.; Kusmiyati, Kusmiyati; Sedijani, Prapti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
This study aims to determine the levels of heavy metal mercury (Hg) in the bodies of Tilapia (Oreochromis niloticus) fish taken from Lake Rawa Taliwang to enrich the material in Ecotoxicology. This study is particularly useful in protecting consumers from heavy metal contamination when consuming fish. This study was conducted at Lake Rawa Taliwang, located in West Sumbawa. There were two separate stations in the study, namely on the east and west sides of the lake. Tilapia (Oreochromis niloticus) fish were caught using gill nets. Three to four fish samples were taken from each station. Each fish sample was then placed in a plastic bag and stored in a sample box. The research samples were then analyzed at the West Nusa Tenggara Health Testing and Calibration Laboratory. Data analysis was carried out by taking fish muscle tissue and analyzing the heavy metal content of Hg using an Atomic Absorption Spectrophotometer (AAS). The wet digestion stage of sample digestion is the process of degrading organic material in the sample using a strong acid, namely HNO3, as a digesting agent. The data obtained is the heavy metal Hg content in ppm (parts per million). The next stage is to process the obtained Hg concentration descriptively and then display it in a table according to the AAS results. The conclusion of this study was that the heavy metal Hg content in Tilapia (Oreochromis niloticus) originating from Lake Rawa Taliwang to enrich the Ecotoxicology material ranged from 0.044 to 0.086 ppm.